Viewing exercise goal content through a person-oriented lens: A self-determination perspective. (November 2016) - Lindwall, Magnus; Weman-Josefsson, Karin; Sebire, Simon J.; Standage, Martyn
Abstract: The present study examined profiles of exercise goal content and the associations with need satisfaction, motivation regulation and exercise behavior, combining variable-centered and person-centered analytical approaches. The participants were 1084 (279 men and 805 women) Swedish adults, aged between 18 and 78 years, that were all active members of an Internet-based exercise program. Latent profile analysis (LPA) and structural equation modeling (SEM) were used to analyze the data. In SEM analysis intrinsic goals were related to need satisfaction and autonomous motivation, whereas extrinsic goals were most strongly associated with controlled motivation. LPA revealed five unique latent classes of goal content. These five classes differed in need satisfaction, motivation regulation and exercise behavior, with classes being characterized by more intrinsic goal profiles reporting higher need satisfaction and autonomous motivation. The results are discussed from a self-determination theory perspective and the benefits of using both variable and person-centered analytical approaches are highlighted. Highlights: Individuals may hold both more intrinsic and extrinsic types of goals for exercise. Different types of goal content is associated with need satisfaction and behavior regulation. Goal content profiles, being combinations of different goals, offer a new way to understand individuals exercise pattern. Individuals with different goal content profiles also differ in need satisfaction and behaviour regulation in exercise.